Sustainability of Rural Tourism and Promotion of Local Development - Ivona, Antonietta (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue contains articles include, but not limited to, empirical, analytical, or design-oriented approaches to the following topics: Monitoring of carrying capacity and mechanisms for managing tourist flows in rural areas; Systems and tools to measure the social, economic, and environmental sustainability of rural tourism; Integration between public tourism policies and private strategies in the promotion and implementation of sustainable practices; Policies for promoting public participation in the planning and development of sustainable rural tourism; The impacts of tourism on traditional agricultural activities; Identity enhancement of the territory and its productions; "Good practices" in the implementation of rural tourism sustainability.